Effect of thymoquinone and thymoquinone-loaded nanostructured lipid carrier in in vitro wound healing model - Alexander, Henna Roshini (2019)
Wound healing is the body’s natural response to wounding. It comprises of four highly integrated phases (haemostasis, inflammation, proliferation and remodelling) resulting in a scar. When there is an impairment to any of the healing components, the healing process gets disrupted and chronic wound ensue. Impaired wound healing is one of the major problems in diabetic patients due to persistence of inflammatory cells and increased apoptosis throughout the healing process. A constant influx of inflammatory cells releases a high level of free radicals such as reactive oxygen species that results in chronic wound. Although the exact mechanism that causes poor wound healing in diabetic patients is unclear, numerous factors have been associated with it, including wound infection, chronic inflammation, sensory neuropathy and hypoxia. Thus, new prospect for therapy to favour speed and optimal healing are emerging. In this study, thymoquinone (TQ), a bioactive compound found in N. sativa seed was loaded into a colloidal drug carrier known as a nanostructured lipid carrier (NLC) producing a compound known as thymoquinone-loaded nanostructured lipid carrier (TQ-NLC) (PATENT NO: PI2012001818). The rapidly progressing nanotechnology today set a new alternative carrier to enhance and favour the speed of healing process. This study aimed to determine the effect of TQ and TQ-NLC on cell proliferation and migration, the mode of cell death and the antioxidant levels in normal and diabetic cell models, 3T3 and 3T3-L1. Cytotoxicity of TQ and TQ-NLC was determined by MTT assay. Based on the MTT assay, the IC10 obtained for 3T3-L1 treated with TQ and TQ-NLC for 24 hours were 5.3 ± 0.6 and 4.7 ± 3.3 μM respectively. As for 3T3 cell, the IC10 obtained for TQ and TQ-NLC at 24 hours were 3.9 ± 2.05 and 4.3 ± 0.17 μM. TQNLC was seen to increase the number of healthy cells (89-95%) and gradually decrease early apoptotic cells in time and dose dependant manner compared to TQ in 3T3-L1 cell in the Annexin V analysis. At 72 hours, 3 μM of treatment with TQ NLC resulted in the highest number of healthy cells. In 3T3-L1 cells treated with TQ, the apoptotic cells decreased from 16.5% to 11.5 % after 72 hours. 3T3-L1 treated with TQ-NLC showed the lowest number of apoptotic cells and a significant increase in healthy cells compared to control at 48 and 72 hours. In the proliferation and migration assay, 3T3-L1 treated with TQ-NLC showed a higher proliferation and rate of migration (p< 0.05) compared to TQ treated cells. In the antioxidant assay, TQ-NLC acted as antioxidant by reducing ROS levels in both the cells after injury at concentration as low as 3 μM. Both the cells treated with TQ-NLC showed a significantly lower level of ROS (p< 0.05) compared to treatment with TQ. Thus, this study demonstrated that TQ-NLC performed better compared to TQ especially on the diabetic mimic cell, 3T3-L1. TQ-NLC accelerated the migration and proliferation of cells while reducing the ROS produced in the wounded cells confirming its ability as a good antidiabetic and antioxidant agent.